Relationship between introversion/extraversion and L2 reading proficiency of Arab undergraduates - Khaoula, Medjedel (2016)
Personality types have a great influence on our lifestyle, attitudes and preferences, as well as our way of learning and academic performance. In the literature, research on introversion/extraversion correlation to reading is insufficient and exposed contradicted findings as well. Therefore, this study tries to draw conclusions about the relationship between ntroversion/extraversion and L2 reading proficiency for Arab undergraduates.And the key issue that has to be considered in this study is investigating which function pair that represent the mental functions (NT, NF, SF or ST) of introversion/extraversion performs the highest reading proficiency score. The present study examines personality types of L1 Arab undergraduates who are ESL learners. Next, the learners’ reading proficiency levels in English were associated with their personality types. Further, the function pairs of both introverts and extraverts that contribute to the highest score of L2 reading proficiency were determined for the learners. This study is anchored on three main theories. From a psychological perspective, Carl Jung’s theory (1923) of Psychological Types which is based on natural preference, is adopted. The theory further posits that these preferences, when used properly, lead to competence and success in the field of education. In addition, Hans Eysenck’s (1967) approach of the biological basis of personality gives a physiological explanation that guides introversion/extraversion preferences. With regard to reading, David Rumelhart’s (1977) interactive model of reading comprehension is adopted to explain the process of reading comprehension and hence, reading proficiency. This model claims that reading includes the use of both higher mental operation and the lower text processing. Participants for the study were randomly selected from the College of Business Administration in Taibah University,Saudi Arabia. Two instruments were used to collect the required data for the study. The first was the Myers-Briggs Type Indicator (MBTI), a self-report questionnaire that helped the participants to determine their personal qualities. The MBTI contains four bipolar dimensions that classify people as either extravert or introvert, thinking or feeling, sensing or intuitive, and judging or perceiving. The second instrument was an English reading test (TOEIC Bridge), which was used to determine the reading proficiency level of the ESL learners. In this test, learners used their knowledge of English grammar, usage, vocabulary as well as reading skills to answer the questions. The data from the reading component of the test was used for the study to find the association between the learners’ reading proficiency in English and their personality type. The collected data was used to address the following research questions: a) Which is the most dominant personality type among L1 Arab undergraduates? b) What is the relationship between students’ introversion and extraversion and their L2 reading proficiency? and c) What are the function pairs of introverted and extraverted types that represented the highest scores of L2 reading proficiency? The findings of the study showed that introversion is the dominant personality type among business ESL undergraduates. Also, no statistically significant relationship between introversion/extraversion and reading proficiency was found.However, the highest reading scores were accompanied with NT and NF function pairs.